Tantangan pemahaman bahasa: Problematika belajar bahasa Arab pada tingkat dasar MI Iskandar Sulaiman - Maulida, Anissa Nur (Maliki Interdisciplinary Journal, 2024)
The purpose of this article is to describe the Arabic language learning problems faced by class V Mi Iskandar Sulaiman students. The difficulties faced in learning Arabic are specific problems that arise during the process of mastering the language. One type of analysis that the author carried out was qualitative. In this research, data collection was carried out using interview observation techniques. In this research In this case, the focus is a fifth grade female student and her Arabic teacher. Data analysis in this research was carried out using qualitative analysis methods, which were carried out before the experiment started, during the experiment, and after the experiment was finished.